1987
DOI: 10.1002/star.19870390903
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Differences in Physicochemical Properties of Waxy Rice Starch

Abstract: High‐gelatinization temperature (GT) waxy rice starch amylopectin has higher sedimentation coefficient than low‐GT waxy rice amylopectin. Get filtration on Sepharose CL‐2B and TSK‐Gel G‐6000PW also showed higher mean molecular weights for high‐GT amylopectins than for low‐GT amylopectins. The harder texture of cooked rice products from high‐GT waxy rices, compared to the texture of products from low‐GT waxy rices, may be due to the higher molecular weight of their amylopectins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Rice varieties whose flour have high gelatinisation temperature hardened more quickly after being gelatinised or made into rice cakes (Yanase et al, 1982;Juliano and Villareal, 1987;Okamoto and Nemoto, 1998;Kobayashi et al, 1999). These varietal differences in gelatinisation and processing were thought to be based on molecular size or structural differences in amylopectin, the sole constituent of waxy rice starch U uliano and Villareal, 1987;Okamoto and Nemoto, 1998;Kobayashi et al, 1999). In this study, we determined whether differences in amylopectin structure between Nipponbare and Kasalath controlled by the major gene acl (t) (Umemoto et al, 2002) affect a major processing property of waxy rice, the rice cake hardening rate.…”
Section: Discussionmentioning
confidence: 99%
“…Rice varieties whose flour have high gelatinisation temperature hardened more quickly after being gelatinised or made into rice cakes (Yanase et al, 1982;Juliano and Villareal, 1987;Okamoto and Nemoto, 1998;Kobayashi et al, 1999). These varietal differences in gelatinisation and processing were thought to be based on molecular size or structural differences in amylopectin, the sole constituent of waxy rice starch U uliano and Villareal, 1987;Okamoto and Nemoto, 1998;Kobayashi et al, 1999). In this study, we determined whether differences in amylopectin structure between Nipponbare and Kasalath controlled by the major gene acl (t) (Umemoto et al, 2002) affect a major processing property of waxy rice, the rice cake hardening rate.…”
Section: Discussionmentioning
confidence: 99%
“…Soaking temperatures closer to the gelatinisation temperature of starch, resulted in greater water uptake. The gelatinisation temperature of Thai glutinous rice has been reported to be between 60 and 70°C (Juliano & Villareal, 1987;Noomhorm et al, 1997;Tester & Morrison, 1990;Varavinit et al, 2003). Takeuchi et al (1997) reported that the gelatinisation rate of long grain rice gradually increases between 60 and 70°C, and saturates around 80°C.…”
Section: Effect Of Temperature On Water Uptake Kineticsmentioning
confidence: 98%
“…In addition, the starch qualities of waxy rice vary greatly (Juliano and Villareal 1987;Bao et al 2004). The distinct divergence in waxy rices is in the gelatinization temperature (GT).…”
Section: Introductionmentioning
confidence: 98%